Nurses Knowledge and Practice Concerning Nursing Management for Patients with Stroke - Haider Al-Abidi; Khalida Mansour (Kufa Journal for Nursing Sciences)
Background: Stroke is the leading cause of mortality and disability worldwide; 87% of all deaths from stroke and 89% of all stroke-related disability-adjusted life-years occur in low- and middle-income countries.